Nanoferrites for Green Magnetic Refrigeration - Casagrande-Denardin, J (Institute of Physics Publishing, 2022)
In this chapter we provide a brief introduction to the magnetocaloric effect, the measurement approaches, and the investigation of the magnetocaloric parameters of different spinel ferrites and ferrite nanocomposites for magnetic refrigeration applications. © IOP Publishing Ltd 2022.